Pengembangan model manajemen risiko berbasis teknologi informasi terhadap nilai perusahaan melalui kinerja di sektor perbankan syariah - istiqomah, azizatul (Maliki Interdisciplinary Journal, 2025)
This study examines the impact of the implementation of information technology-based risk management models on the performance and value of companies in the Islamic banking sector. The Islamic banking industry faces challenges in balancing business growth and effective risk management in the digital age, compounded by the need to comply with sharia principles in addition to conventional banking regulations. The main problem faced is integrating information technology in the risk management system to improve operational efficiency, decision-making accuracy, and ultimately company value. The information technology-based risk management model includes system integration, process automation, advanced data analytics, real-time risk monitoring, and digital risk reporting. Company performance, measured through financial, operational, and risk performance, serves as a mediating variable that links the implementation of an information technology-based risk management model to the company's value. The company's value is measured through market-based and accounting indicators, as well as stakeholder value. This research shows that information technology-based risk management models improve organizational risk performance through integrated systems that enable more effective and efficient risk management. The implementation of IT-powered Enterprise Risk Management (ERM) Systems positively impacts operational efficiency, profitability, and competitive advantage, as well as increases stakeholder trust and protection of sensitive information. Information technology serves as an enabler and moderator, enabling a more sophisticated level of risk management with greater accuracy and speed.